Pumakkal formula for making shrimp pond waste fertiliser - Sutanto, Agus; Sari, Kartika; Santoso, Handoko; Widowati, Hening; Fidiastuti, Hasminar Rachman; Rukayadi, Yaya (Jambi University, 2024)
One way to decompose the pond waste sediment is to use the liquid nutrient culture media (NB) called Pumakkal as a starter formula. However, bioremediation in shrimp ponds paid less attention despite being massively promoted by the official government. East Lampung produced 11.6 million m3 of liquid waste and 4.077 m3 of sediment waste in shrimp ponds rich in organic matter. However, they will poison the pond if they are unchecked. This study investigated how Pumakkal decomposed shrimp pond waste with three parameters: macronutrients, micronutrients, and pH. The study employed laboratory experiments, and the research was a completely randomised design (CRD) with 15 factorial arrangements. The sample was 65 kg of shrimp pond waste and 65 litres of liquid waste. They were analysed with five treatment experiments: three treatments of liquid waste media (LW), sediment waste (SW), and mixed liquid and sediment waste (MLS). The results showed that the treatment of the CE 15 isolate (with MLS significantly improved (p<0.05) fertiliser quality. Bioremediation using Pumakkal CE is the best treatment with MLS, obtaining the fertiliser with the best macronutrient: Nitrogen (N) 1,3%, Phosphorus (P)2,3%, and Potassium (K) 2,3%; C-organic 23%, C/N ratio 29; micronutrient: Fe:155 ppm, Cu: 51 ppm, Zn: 72 ppm, Mn; 51 ppm, B; 25 ppm, and Mo: 8 ppm, and pH 5-6. The mixture of liquid and pond sediment waste produces the best fertiliser suitable for plant fertiliser users. The study implies that Pumakkal applies to decomposing harmful waste sediment to support the bioremediation program.